Social Cost of Motorcycle Transport on Human Welfare in Kakamega Municipality, Kenya - Akala , Ben M.; Adano , Wario R.; Akala , Winston J.; Ngaira , Josephine K. W. (African Journal of Education,Science and Technology (AJEST), 2014)
Road transport is the centre nerve of movement of passengers, goods and services in urban centers globally. Conventionally, vehicles and handcarts adequately served Kenya‟s towns before the advent of bicycle transport in 1990s that graduated to motorcycle transport (MT) in 2000. Currently, MT dominated intra-urban transport notwithstanding their associated social cost. Regrettably, no policy exists on MT in Kenya to optimize its utility. This paper examined the social cost of MT on human welfare in Kakamega municipality, Kenya. A questionnaire was randomly self-administered to sample of 200 households within the municipality‟s four sub-locations proportionately to obtain primary data. Oral interview, ocular observation and focused group discussions provided additional data. Secondary sources of data were also consulted. Tables, Two Stage Least Squares (2SLS) regression, Pearson‟s correlation coefficient and willingness to pay analysis were used to analyze data The study reveal that MT operated in an unstable, risky, more risky, and most risky environment that aggravated social cost. Two stages Least Square regression model revealed that the variables studied accounted for 64% of the social cost of MT. Consequently, out of the eleven examined factors eight were significant (at P<0.05 level). Human death, urban traffic congestion, overspending, Crime and overloading bore positive coefficients while contrary to the expected, ill health, over speeding and competition had negative coefficients. Finally, Pearson‟s correlate coefficient established a moderate negative relationship between the social cost of MT and human welfare and thus, each household was willing to pay Kshs. 90.80 per month to streamline MT. The study concluded that MT harmed human welfare. It recommended collective responsibility in the management of MT as a strategy to minimize social cost, attain optimal urban MT and better human welfare in Kakamega municipality.